(untitled) («Наука и здравоохранение», 2025)
Introduction. Self-harm and suicide attempts are critical global health challenges that significantly impact adolescents. Adolescents are particularly vulnerable to psychological distress, which often manifests as self-harm, a behavior strongly linked to disorders such as depression, anxiety, and emotional dysregulation. The aim is to summarize the findings from the 2024 report by the Swedish Agency for Health Technology Assessment and Assessment of Social Services (SBU) on interventions to prevent self-harm and suicide attempts in adolescents. Materials and methods. The analysis included 28 randomized controlled trials, along with systematic reviews and meta-analyses, covering a range of interventions for adolescents aged 12 to 18 who had a documented history of self-harm or suicide attempts. Results. Dialectical Behavior Therapy for Adolescents (DBT-A) has been shown to reduce the recurrence of self-harm behaviors significantly. It is well-received by adolescents and their families, with a four-month program offering cost-effective outcomes compared to usual care. Internet-based Emotional Regulation Individual Therapy for Adolescents (IERITA), based on DBT-A, may reduce non-suicidal self-injury (NSSI), though more randomized studies are needed to confirm its efficacy. Adolescents who identify as part of a sexual minority, those with risky substance use, and those in the juvenile justice system have an increased risk of self-harm. However, there is a lack of targeted prevention studies for these groups. Further research is required on interventions that enhance safety following a suicide attempt, such as the SAFETY family intervention and the value of patient-driven admissions in acute care settings. Conclusion. The results indicate the potential to expand access to effective treatments like DBT-A beyond metropolitan areas. Additionally, IERITA may complement existing care for adolescents without immediate suicide risk.